PENGEMBANGAN JAMUR TIRAM DENGAN TEKNOLOGI TEMPERATURE AND HUMIDITY CONTROL DAN OPTIMASI PADA PRODUKSI JAMUR TIRAM - Alvida Mustika Rukmi; M. Isa Irawan; Aunurohim . (JPM17: Jurnal Pengabdian Masyarakat, 2016)
Oyster mushroom cultivation in Kampung Tinja Keputih, can be analternative to empower local communities to be more productive society. Theeconomic value of the oyster mushroom in the area around the target society,with ease and cheapness of oyster mushroom seeds, allowing it to be used asagricultural products in the target area. While the lack of knowledge formushroom cultivation in the lowlands become the forerunner of mushroomcultivation program with tools "Temperature and Humidity Control (THC)â€ sothat the humidity wil meet the plants need extra humidity. This tool will work tooptimize the growth of oyster mushrooms. Field observations of thecharacteristics of the society, climate, fresh water supply and land used as aplace of cultivation. Dissemination was executed to introduce thecharacteristics of oyster mushrooms for the society. Basic training wasorganized to foster interest and motivation of the target communities followedby technical training oyster mushroom cultivation with THC tool support.Optimization of production control aims for a balance of mushroom seed stockand the products that can be marketed. The role of technology is expected tohave an impact to build a society that is constantly innovating character.Results of oyster mushroom cultivation in the target areas will be hope for thetargeted communities and surrounding region in increasing the economic valueand productivity levels of inmates.